Вплив типу субстрату на обкорінення живців двох видів фуксії – Fuchsia magellanica Lam. та F. triphylla L. - Melnik, M.A.; Lyakh, V.O.; Dubova, O.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The results of studing influence of different substratum (water, sand, peat and perlite) on shoot rooting of two species of fuchsia – Fuchsia magellanica Lam. and Fuchsia triphylla L. are presented. It was established that Fuchsia magellanica formed roots better in perlite and sand, while Fuchsia triphylla – in peat and perlite. Fuchsia triphylla formed larger roots per shoot in comparison with Fuchsia magellanica in all substrata.